Incidence of Young People Mental Health Disorders with Atopic Dermatitis during the COVID-19 Pandemic - Alison Monserrat Culqui Tapia; Kerlly Sheylin Rivas Esquivel; Iruma Alfonso González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: atopic dermatitis is a chronic inflammatory dermatological disease that produces structural and functional alteration in the outermost layer of the epidermis. There are certain factors that worsen your symptoms and are related to depression and anxiety linked to emotional stress. Objective: to evaluate the incidence of mental health disorders in patients with atopic dermatitis during the COVID-19 pandemic to establish protection parameters in people belonging to the city of Latacunga. Methods: a descriptive cross-sectional study was carried out in the period from January 2021 to August 2022. The study population consisted of 25 patients from the ZENSE Health Center of the Latacunga Dermatology Clinic, Cotopaxi, Ecuador. The variables studied were: age, sex, modality of confinement during the pandemic, psychological disorders present during COVID-19, predominant symptoms, severity of dermatitis, and areas with the greatest disease. A structured survey was applied to collect the data. The data is presented in tables and graphs, absolute and relative frequencies. Results: the predominant symptoms were those corresponding to the anxious state, with a worsening due to psychological factors. Patients diagnosed with atopic dermatitis influenced by psychological disorders are more likely to develop poor quality of life, the female sex is more susceptible to suffering from this pathology. The predominant symptomatology was itching located on the back of the hands and feet. Conclusions: during the stage of confinement by COVID-19, mental health has been affected and with it the worsening of various psychological disorders that later affect skin manifestations such as atopic dermatitis.